The stability of Islamic finance : creating a resilient financial environment for a secure future - Askari, Hossein (Singapore : John Wiley & Sons, 2010)
The book's main focus is on the question of the sources of financial instability which seems inherent in the conventional system. As a core component of this focus, the book will consider episodes of turbulence and instability in a historical context recalling the occurrence of such events from mid-19th century to the present
1. The nature of capital and the rate of return -- 2. The origins of financial panics and recessions -- 3. Monetary policy and financial crises -- 4. The internationalization of financial crises -- 5. The role of the credit multiplier in financial crises -- 6. The inherent stability of Islamic finance -- 7. A theoretical model of the inherent stability of Islamic finance -- 8. Asset pricing and risk in Islamic finance -- 9. Islamic financial intermediation and markets -- 10. Risk profile of Islamic financial intermediaries -- 11. Financial engineering, derivatives and financial stability -- 12. Corporate governance and financial crises -- 13. The performance of Islamic financial intermediaries and products
Series statement from jacket
Includes bibliographical references (p. 217-223) and index
Keywords: Economic stabilization; Finance -- Religious aspects -- Islam; Finance -- Arab countries; Financial crises -- History